Indoor Air Concentration from Selective Laser Sintering 3D Printer using Virgin Polyamide Nylon (PA12) Powder: A Pilot Study - Muhamad Damanhuri, Amir Abdullah; Hariri, Azian; Alkahari, Mohd Rizal; Md Fauadi, Muhammad Hafidz Fazli; Zainal Bakri, Siti Farhana (International Journal of Integrated Engineering, 2019)
Environmental emission from additive manufacturing (AM) have attracted much attention recently. The capability in fabricating complex part make AM famous in developing prototype and product in various industries especially in aerospace, medical, automotive, and manufacturing industries. However, the study on emission and exposure mainly focusses on the desktop type such as fused deposition modelling. This study investigates the emission and indoor concentration from powder bed fusion of selective laser sintering (SLS) technologies. Prior to the investigation, virgin PA12 undergone characterization in terms of morphology, size and thermal analysis. Calibration block using virgin polyamide nylon (PA12) are selected to be printed in this study. Parameters such particulate matter size 2.5 Âµm (PM 2.5), total volatile organic compound (TVOC), carbon dioxide (CO2), formaldehyde, temperature and relative humidity (RH) are set to be monitored through real time sampling of 8 hours based on Industry Code of Practice on Indoor Air Quality 2010 by Department Occupational Safety and Health (DOSH) Malaysia. Four phases of printing process involve are background data, preprinting, during printing and post printing. Based on the study it was found that PM 2.5 and CO2 exceed the acceptable limit recommended by DOSH Malaysia during preparation of powder (preprinting) at 1218 ppm and 1070 Âµg/m3 respectively. Meanwhile TVOC concentration was influence by the sintered powder temperature and recorded at 0.5 ppm. Temperature, relative humidity and formaldehyde were maintained throughout the SLS process. Mitigation strategies using mechanical ventilation and personal protective equipment (PPE) are recommended to be used to reduce potential of occupational hazard to the operators.